Analisis Digital Marketing Dalam Penggunaan Aplikasi Instagram (Studi Kasus Akun Instagram @vocasia) - Elsha Eriadisvi; Endang Taufiqurahman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Digital marketing is one of the main pillars in providing convenience in doing business, especially on social media such as Instagram, Twitter, Facebook, Tiktok and others. One of the most popular social media today is Instagram. The phenomenon of using social media Instagram for digital marketing which is growing rapidly is utilized by business actors, especially PT Vocasia Eduka. The purpose of this research is to explore digital marketing techniques on @vocasia's Instagram. The research method used when conducting this research was qualitative by selecting case studies as an approach to research. The results of research conducted on the @vocasia Instagram account are in the form of digital marketing analysis in using the right content ideas. The benefit of the presence of this research is to provide new insights about digital marketing on Instagram social media.